Consideraciones sobre el papel de la Península Ibérica en la política religiosa a comienzos del siglo IV - Barceló, Pedro (Antigüedad y Cristianismo, 1991)
A survey of the opinions on the inicial inclusion of the Iberian Peninsula in Constantine's heritage is undertaken and new arguments favouring the thesis of the rule of this Emperor over Hispania since 306 are offered. This helps to determine more exactly the relation between such a circunstance and Constantine's politics and religious legislation; his tolerance towards the Christians seems to begin earlier than has been thought, probably in the middle of 306.